Adaptive Uninterrupted Communication Algorithm for Wireless Mesh Network by Using UV-Rays and Dijkstra’s Algorithm - Kumar, Ajay; Vaid, Rohit (International Journal of Computer Sciences and Engineering, 2025)
Now a day’s wireless sensor networks are the main source of communication, so it is an important area of research. The main issues of wireless sensor networks are energy consumption and communication consistency. In this research paper the energy is reducing by minimizing the distance between sensor nodes and increases the accuracy of message transfer. An adaptive uninterrupted communication algorithm is proposed to maintain the consistency of network by using wireless mesh network topology. Mesh topology is used as it is a less expensive network than traditional network, it is extremely adaptive and expandable and it also supports high demand. UV-rays are used to data transmission in wireless mesh network since UV-links can give faster communication rate. In this research paper dijkstra’s algorithm is used to find out the shortest path between source and destination nodes, so that as the distance between the sensors nodes are minimised as a result less energy is used in wireless mesh network communication (E d2).